Impacts of extreme climate events on vegetation succession at the northern foothills of Yinshan mountain, inner Mongolia - Zhou, Pingping; Liao, Zilong; Song, Xiaoyan; Li, Wenya; Feng, Yaru; Sun, Wenyi; Mu, Xingmin; Zhai, Jun; Zhou, Haili (Frontiers in Environmental Science, 2025)
Extreme climate events significantly impact vegetation ecosystems in dry regions, particularly in areas adjacent to the northern foothills of Yinshan Mountain (NYSM). However, there remains limited understanding of how vegetation responds to such events. Analyzing the response of vegetation in dry regions to drought is beneficial for the protection and restoration of the vegetation ecosystem. This study analyzes the spatiotemporal variation characteristics of extreme climate events and NDVI. By employing correlation analysis and geographic detectors, it explores the response of vegetation NDVI to extreme climate events. The findings indicate a recent decline in extreme temperature events and a concurrent rise in extreme precipitation events. From 2000 to 2020, NDVI demonstrated consistent improvement, a trend expected to persist in the future. Extreme temperature events exhibited a strong negative correlation with NDVI, whereas extreme precipitation events demonstrated a strong positive correlation. Furthermore, extreme precipitation events possess greater explanatory power for NDVI variability compared to extreme temperature events. The research findings provide a theoretical basis for the different vegetation types in NYSM to respond to extreme climate events, and they inform targeted ecological restoration measures based on the varying responses of different vegetation types to these extreme climate events.